2010
DOI: 10.1007/s12032-010-9463-x
|View full text |Cite
|
Sign up to set email alerts
|

Weight gain after adjuvant chemotherapy in patients with early breast cancer in Istanbul Turkey

Abstract: Weight gain is a well-known and unwanted complication of adjuvant chemotherapy in breast cancer. We observed that the female Turkish cancer patients frequently gain weight with adjuvant treatment of breast cancer and planned to examine the magnitude of this problem in early breast cancer patients treated at our hospital. A total of 176 early breast cancer patients who received their adjuvant systemic therapy in Marmara University Hospital between 2003 and 2007 are included in the study. We recorded their weigh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
10
1
1

Year Published

2012
2012
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 22 publications
(12 citation statements)
references
References 38 publications
0
10
1
1
Order By: Relevance
“…Moreover, our results also identified weight at diagnosis as an independent negative predictive factor for weight gain (r=-0.355, B=-3.748, P<0.05), with a weak linear correlation (r=-0.355, R 2 = 0.126, P<0.05). The menopausal status was previously reported to be a positive predictor for weight gain in women receiving adjuvant chemotherapy (24)(25)(26), although it was also reported that menopausal status did not affect body weight (27). Our data suggested that there was no significant correlation between menopausal status and weight changes in Chinese breast cancer patients following adjuvant chemotherapy.…”
Section: Linear Correlation Linear Regressioncontrasting
confidence: 44%
“…Moreover, our results also identified weight at diagnosis as an independent negative predictive factor for weight gain (r=-0.355, B=-3.748, P<0.05), with a weak linear correlation (r=-0.355, R 2 = 0.126, P<0.05). The menopausal status was previously reported to be a positive predictor for weight gain in women receiving adjuvant chemotherapy (24)(25)(26), although it was also reported that menopausal status did not affect body weight (27). Our data suggested that there was no significant correlation between menopausal status and weight changes in Chinese breast cancer patients following adjuvant chemotherapy.…”
Section: Linear Correlation Linear Regressioncontrasting
confidence: 44%
“…9 Moreover, one study showed that patients with breast cancer and patients receiving chemotherapy had increased levels of anxiety and depression compared with those with cancer at other sites and other treatment regimens. 10 Barring mental health issues, weight gain 11 and sleep disruption 12 occur very often during chemotherapy, threatening the general health status of patients.…”
Section: Introductionmentioning
confidence: 99%
“…, Basaran et al . ) and bothersome physical symptoms (McInnes & Knobf ) in women with breast cancer who receive adjuvant chemotherapy. Over 60% of patients with breast cancer reported a 5% weight gain following chemotherapy (Saquib et al .…”
Section: Introductionmentioning
confidence: 99%